Mind the ESG gaps: Transmission mechanisms and the governance of and by sustainable finance - Jan Fichtner; Robin Jaspert; Johannes Petry (Danish Institute for International Studies (DIIS), 2023)
Environmental, social and governance (ESG) funds are among the fastest growing investment styles. ESG funds can be used either to only mitigate risk (input ESG) or to go beyond that to create impact (output ESG). We argue that the governance by ESG is characterised by three potential transmission mechanisms: ratings, shareholder engagement and capital allocation. These mechanisms can create sustainability impact or constitute 'ESG gaps', if they remain ineffective or unutilised. Based on financial data, an investigation of ESG methodologies and expert interviews, we provide a novel market analysis of the ESG industry, focusing primarily on the capital allocation mechanism. Our findings highlight that while ESG indices could have an impact, most currently do not meaningfully facilitate sustainability - we call this the 'ESG capital allocation gap'. This has important implications because without effective transmission mechanisms, ESG funds cannot have sustainability impact on companies and the real economy.
Keywords: 330; Capital allocation; ESG; impact; sustainable finance; transmission mechanisms